Optimizing spotting solutions for increased reproducibility of cDNA microarrays - Rickman, David S. (Oxford University Press, 2003)
The ability to extract meaningful information from transcriptome technologies such as cDNA microarrays relies on the precision, sensitivity and reproducibility of the measured values for a given gene across multiple samples. Given the lack of a ‘gold standard’ for the production of microarrays using current technologies, there is a high degree of variation in the quality of data derived from microarray experiments. Poor reproducibility not only adds to the cost of a given study but also leads to data sets that are difficult to interpret. For glass slide DNA microarrays, much of this variation is introduced systematically, during the spotting, or deposition, of the DNA onto the slide surface. In order to reduce this type of systematic variation we tested spotting solutions containing different detergent additives in the presence of one of two different denaturants and determined their effect on spot quality. We show that spotting cDNA in a solution consisting of the zwitterionic detergent 3-[(3-cholamidopropyl)dimethylammonio]-1-propane sulfonate (CHAPS) in the presence of formamide or dimethyl sulfoxide yields spots of superior quality in terms of morphology, size homogeneity and signal reproducibility, as well as overall intensity, when used with popular, commercially available slides.